IPO Underpricing: Financial Vulnerability and Corporate Financial Behavior Disclosure - Gesti Memarista; Kevin Effendy; Nayeon Kim (Universitas Pendidikan Nasional, 2026)
By examining the effects of financial vulnerability, corporate financial conduct, profitability, and company size on IPO underpricing, the research aimed to clarify how IPO pricing was affected by firm-level financial features and how the market responded to these financial signals. A regression analysis across several model specifications was applied to 268 Indonesian non-financial public companies from 2017 to 2025, which experienced underpricing on the first day of their IPOs. The findings demonstrated that underpricing was positively associated with financial fragility in the baseline model but became negligible in the extended models, suggesting that the effect varied with firm characteristics. Underpricing was consistently and negatively affected by corporate financial behavior, indicating that improved financial discipline reduced information asymmetry and boosted investor confidence. Underpricing was found to be positively impacted by profitability, indicating that better financial results were linked to higher investor demand, as evidenced by underpricing results. On the other hand, firm size had a negative impact; thus, with less ambiguity, larger firms underpriced less. Overall, the results showed that, in addition to fundamentals, investor behavior, as inferred from market responses to financial signals, also affected IPO underpricing. The findings highlight the managerial implications of maintaining financial discipline for businesses preparing to go public, as evidenced by improved corporate financial behavior aimed at reducing underpricing. The practical implication is that investors must carefully assess profitability signals and avoid overreacting, as overreaction can lead to mispricing, especially in developing countries like Indonesia. The study also emphasizes the importance of strengthening transparency and disclosure rules to help regulators and legislators reduce information asymmetry and improve market efficiency.